Sistem Penerimaan dan Pengelolaan Santri Baru di Santri Privat Yayasan Santri Cendekia - Nur Haimah (Jurnal Pengabdian Masyarakat: Tipis Wiring, 2024)
Abstract This journal discusses the implementation and evaluation of the admission and management system for new students at Santri Privat, Yayasan Santri Cendekia. The research aims to enhance the efficiency and effectiveness of the admission and management processes for new students within the foundation's environment. The research method employed involves observation, interviews, and analysis of relevant policies and procedures. The results of the study indicate that the implementation of the admission and management system for new students at Santri Privat, Yayasan Santri Cendekia, has positively contributed to the selection and administrative processes. This system utilizes information technology to support the registration, selection, and management of student data. Consequently, time and resources required can be managed more efficiently. Furthermore, the research identifies some challenges faced by the system, such as the need for technology updates and training for related staff. Therefore, continuous improvement and updates are necessary to ensure the sustainability and reliability of the system. With the improvement in the admission and management system for new students, it is expected that Yayasan Santri Cendekia can provide better educational services and ensure the well-being of new students in supporting their potential and character development. This research provides valuable insights for similar institutions seeking to enhance the efficiency of admission processes and student data management.